Educational Video-Based Play Methods in Physical Education Learning: Social Emotional of Children with Special Needs - Hasmyati, Hasmyati; Anwar, Nur Indah Atifah; Syafruddin, Muhammad Akbar; Hamzah, Alimin (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study is an experimental approach that utilizes educational video-based play methods to enhance the social-emotional skills of children with special needs through physical education learning. This study employs a single-group pretest-posttest research design. The number of samples in this study was 23 children with special needs. The data collection technique employed a social emotional questionnaire, which consisted of 15 statements provided to parents of students and had a Cronbach's Alpha instrument reliability of 0.952. We used a paired sample t-test for the data analysis technique. The results of the data analysis showed that the Sig. data value was 0.001 < 0.05. Therefore, we can conclude that the pre-test and post-test data on the social-emotional aspects of children with special needs differ. Furthermore, the mean value of the pre-test social-emotional data was 45.04, while the mean value of the post-test social-emotional data was 52.13, resulting in a mean difference of 7.087. Based on these results, we can conclude that the video-based play learning method in physical education influences the social-emotional aspects of children with special needs. Meanwhile, the results of the N-Gain test show that the effectiveness of the video-based play method in physical education learning to improve the social emotions of children with special needs is in the moderate category.